Association between Obesity and Lipid Profile among Patients with Type 2 Diabetes Mellitus at a Tertiary Care Hospital in Eastern Nepal - Pokharel, Karan; Bhandari, Shraddha; Mahato, Uday Kumar; Mishra, Gopal (Journal of Bharatpur Hospital, 2026)
BackgroundType 2 Diabetes Mellitus (T2DM) is frequently associated with obesity and dyslipidemia, major risk factors for cardiovascular disease. However, evidence on their prevalence and relationship among T2DM patients in Eastern Nepal is limited. This study aimed to determine the prevalence of obesity and dyslipidemia and assess the association between Body Mass Index (BMI) and lipid profile parameters among T2DM patients attending a tertiary care hospital in Eastern Nepal.MethodsThis hospital-based cross-sectional observational study was conducted from February 2026 to March 2026.Enrolled 405 adult patients with Type 2 Diabetes Mellitus (T2DM) attending the Medical Outpatient Department (OPD) of B & C Medical College Teaching Hospital & Research Center. Sociodemographic and clinical data were collected using a structured questionnaire. Anthropometric measurements were performed and fasting lipid profiles were obtained from routine laboratory investigations. Data were analyzed using STATA version 14. Chi-square tests, one-way ANOVA, and multivariate logistic regression were used to assess associations.ResultsThe mean age of participants was 52.4 ± 11.8 years, and 44.7% were obese (BMI ≥25 kg/m²). Dyslipidemia was present in 79.3% of patients, with elevated LDL-C (75.8%) being the most common abnormality, followed by hypertriglyceridemia (62.0%), elevated total cholesterol (56.3%), and low HDL-C (53.8%). Obese patients had significantly worse lipid profiles than non-obese patients (p